The Court Comedies of John Lyly : A Study in Allegorical Dramaturgy - Saccio, Peter (Princeton, NJ : Princeton University Press, 2015)
The nature of Renaissance allegory has been the subject of much investigation, notably by Spenserian scholars. The subject is now enlarged through a study of the plays of the Elizabethan Court dramatists of the 1580's and early 1590's, particularly the comedies of John Lyly. Mr. Saccio rejects the older "topical readings" of Lyly; by extensive interpretation of particular plays he describes three distinct kinds of allegorical operation apparent in successive phases of Lyly's career and suggests that they form an important paradigm of the development of English drama itself.Originally published in 1969.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- ACKNOWLEDGMENTS -- CONTENTS -- INTRODUCTION -- I. A STAGE FOR ALLEGORY -- I I . THE WORLD OF CAMPASPE -- III . THE GODS OF GALLATHEA -- IV. CUPIDS, COURTS, AND THE QUEEN -- V. TRANSITION TO NARRATIVE -- APPENDIX -- INDEX
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Allegory; Comedy; Courts and courtiers in literature; English drama (Comedy) -- History and criticism; LITERARY CRITICISM / Drama